Analisis Strata Norma Roman Ingarden dalam Puisi “Doa Seorang Pesolek” Karya Joko Pinurbo - Dania Kusuma Wardani; Wawan Hermawan; Taufiq Hidayat; Salsa Devista Mayangsari; Misbahul Khanif (Journal Innovation In Education, 2025)
This research is a qualitative descriptive study with the aim of analyzing the use of Roman Ingarden norm strata in the poem "Doa Sebuah Pesolek" by Joko Pinurbo, especially in the sound stratum, meaning units, the represented object, the represented world, and metaphysical qualities. This research focuses on the interpretation and meaning of readers towards literary objects based on the five layers. Data collection techniques use reading techniques and note-taking techniques. Data analysis techniques use content analysis, which is done by observing the contents of the poem to indicate 5 norm strata. The stages of data analysis begin with examining the ontology of the poem, analyzing the poem, and verifying the research results. The research findings show that each norm layer appears in an integrated manner and forms a complete meaning, and opens up new interpretations of the existential side of human life between the body, spiritual, and meaning of life.